2019
DOI: 10.29076/issn.2528-7737vol12iss29.2019pp9-19p
|View full text |Cite
|
Sign up to set email alerts
|

Fitoquímica De Lippia Citriodora K cultivada en Ecuador y su actividad biológica.// Phytochemistry of Lippia citriodora K grown in Ecuador and its biological activity

Abstract: Se realizó un estudio fitoquímico de metabolitos secundarios, actividad antimicrobiana y letal del extracto metanólico de las partes botánicas de Lippia citriodora K (cedrón). Se detectó la presencia taninos, polifenoles, triterpenos y esteroles insaturados para las hojas, flores y tallo; fenilpropanoides y catequinas para tallos y flores; alcaloides para hojas y flores; saponinas para  hojas y tallos. Además, las flores exhibieron la presencia de cumarinas y metilencetonas. Todos los extractos metanólicos mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Different results were observed in the study with methanol/water extract of L. multiflora where high toxicity was verified, presenting LC50 result of 1.1 µg/mL (AJAIYEOBA et al, 2006). The analysis of methanolic extracts prepared with different parts (stem, leaf and flowers) of L. citriodora showed that all extracts present significant lethality against A. salina, being its composition rich in tannins, polyphenols, triterpenes, catechins and alkaloids (VÉLEZ et al, 2019).…”
Section: Resultsmentioning
confidence: 84%
“…Different results were observed in the study with methanol/water extract of L. multiflora where high toxicity was verified, presenting LC50 result of 1.1 µg/mL (AJAIYEOBA et al, 2006). The analysis of methanolic extracts prepared with different parts (stem, leaf and flowers) of L. citriodora showed that all extracts present significant lethality against A. salina, being its composition rich in tannins, polyphenols, triterpenes, catechins and alkaloids (VÉLEZ et al, 2019).…”
Section: Resultsmentioning
confidence: 84%